Psychosocial factors in indoor work-related symptoms. Application of the MM040/IAQ questionnaire - Magnavita, Nicola (La Medicina del Lavoro, 2014)
Aims: To study the relationship between psychosocial factors and the perception of the work environment by means of a questionnaire and to evaluate the efficacy of using a questionnaire for contributing to the solution of environmental problems and for monitoring work-related stress. Methods: Before the routine medical examination, the occupational physician administered questionnaires to all the employees who had been working at least one year in an indoor environment in 28 companies. 4,029 out of 4,129 subjects participated (97.6%). Results: There was a significant association between psychosocial factors and perception of the work environment. The association between psychosocial factors and symptoms was also significant. Conclusions: Results confirmed the role of psychosocial factors in the perception of the work environment and in the attribution of symptoms to occupational exposure, without excluding the possibility that symptoms were actually caused by occupational exposure. The questionnaire proved to be a valid tool for monitoring perceived occupational stress.